5.3.10 Problems 901 to 1000

Table 5.303: Second order ode

#

ODE

Mathematica

Maple

3589

\[ {}y^{\prime \prime } = x \,{\mathrm e}^{x} \]

3590

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

3591

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }-8 y = 0 \]

3592

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = \ln \left (x \right ) x^{2} \]

3631

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x} = 9 x \]

3696

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 0 \]

3697

\[ {}y^{\prime \prime }+7 y^{\prime }+10 y = 0 \]

3698

\[ {}y^{\prime \prime }-36 y = 0 \]

3699

\[ {}y^{\prime \prime }+4 y^{\prime } = 0 \]

3707

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }-8 y = 0 \]

3708

\[ {}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+y = 0 \]

3711

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 18 \,{\mathrm e}^{5 x} \]

3712

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 4 x^{2}+5 \]

3716

\[ {}y^{\prime \prime }+y = 6 \,{\mathrm e}^{x} \]

3717

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 5 x \,{\mathrm e}^{-2 x} \]

3718

\[ {}y^{\prime \prime }+4 y = 8 \sin \left (2 x \right ) \]

3719

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 5 \,{\mathrm e}^{2 x} \]

3720

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 3 \sin \left (2 x \right ) \]

3724

\[ {}y^{\prime \prime }+9 y = 5 \cos \left (2 x \right ) \]

3725

\[ {}y^{\prime \prime }-y = 9 \,{\mathrm e}^{2 x} x \]

3726

\[ {}y^{\prime \prime }+y^{\prime }-2 y = -10 \sin \left (x \right ) \]

3727

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 4 \cos \left (x \right )-2 \sin \left (x \right ) \]

3728

\[ {}y^{\prime \prime }+\omega ^{2} y = \frac {F_{0} \cos \left (\omega t \right )}{m} \]

3729

\[ {}y^{\prime \prime }-4 y^{\prime }+6 y = 7 \,{\mathrm e}^{2 x} \]

3732

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = \sin \left (x \right )^{2} \]

3733

\[ {}y^{\prime \prime }+6 y = \sin \left (x \right )^{2} \cos \left (x \right )^{2} \]

3734

\[ {}y^{\prime \prime }-16 y = 20 \cos \left (4 x \right ) \]

3735

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 50 \sin \left (3 x \right ) \]

3736

\[ {}y^{\prime \prime }-y = 10 \,{\mathrm e}^{2 x} \cos \left (x \right ) \]

3737

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 169 \sin \left (3 x \right ) \]

3738

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 40 \sin \left (x \right )^{2} \]

3739

\[ {}y^{\prime \prime }+y = 3 \,{\mathrm e}^{x} \cos \left (2 x \right ) \]

3740

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 2 \sin \left (x \right ) {\mathrm e}^{-x} \]

3741

\[ {}y^{\prime \prime }-4 y = 100 x \,{\mathrm e}^{x} \sin \left (x \right ) \]

3742

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 4 \,{\mathrm e}^{-x} \cos \left (2 x \right ) \]

3743

\[ {}y^{\prime \prime }-2 y^{\prime }+10 y = 24 \,{\mathrm e}^{x} \cos \left (3 x \right ) \]

3744

\[ {}y^{\prime \prime }+16 y = 34 \,{\mathrm e}^{x}+16 \cos \left (4 x \right )-8 \sin \left (4 x \right ) \]

3745

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 4 \,{\mathrm e}^{3 x} \ln \left (x \right ) \]

3746

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{-2 x}}{x^{2}} \]

3747

\[ {}y^{\prime \prime }+9 y = 18 \sec \left (3 x \right )^{3} \]

3748

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = \frac {2 \,{\mathrm e}^{-3 x}}{x^{2}+1} \]

3749

\[ {}y^{\prime \prime }-4 y = \frac {8}{1+{\mathrm e}^{2 x}} \]

3750

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = {\mathrm e}^{2 x} \tan \left (x \right ) \]

3751

\[ {}y^{\prime \prime }+9 y = \frac {36}{4-\cos \left (3 x \right )^{2}} \]

3752

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = \frac {2 \,{\mathrm e}^{5 x}}{x^{2}+4} \]

3753

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 4 \,{\mathrm e}^{3 x} \sec \left (2 x \right )^{2} \]

3754

\[ {}y^{\prime \prime }+y = \sec \left (x \right )+4 \,{\mathrm e}^{x} \]

3755

\[ {}y^{\prime \prime }+y = \csc \left (x \right )+2 x^{2}+5 x +1 \]

3756

\[ {}y^{\prime \prime }-y = 2 \tanh \left (x \right ) \]

3757

\[ {}y^{\prime \prime }-2 m y^{\prime }+m^{2} y = \frac {{\mathrm e}^{m x}}{x^{2}+1} \]

3758

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {4 \,{\mathrm e}^{x} \ln \left (x \right )}{x^{3}} \]

3759

\[ {}y^{\prime \prime }+2 y^{\prime }+y = \frac {{\mathrm e}^{-x}}{\sqrt {-x^{2}+4}} \]

3760

\[ {}y^{\prime \prime }+2 y^{\prime }+17 y = \frac {64 \,{\mathrm e}^{-x}}{3+\sin \left (4 x \right )^{2}} \]

3761

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {4 \,{\mathrm e}^{-2 x}}{x^{2}+1}+2 x^{2}-1 \]

3762

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 15 \,{\mathrm e}^{-2 x} \ln \left (x \right )+25 \cos \left (x \right ) \]

3767

\[ {}y^{\prime \prime }-9 y = F \left (x \right ) \]

3768

\[ {}y^{\prime \prime }+5 y^{\prime }+4 y = F \left (x \right ) \]

3769

\[ {}y^{\prime \prime }+y^{\prime }-2 y = F \left (x \right ) \]

3770

\[ {}y^{\prime \prime }+4 y^{\prime }-12 y = F \left (x \right ) \]

3771

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 5 \,{\mathrm e}^{2 x} x \]

3772

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

3773

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = 4 \ln \left (x \right ) \]

3774

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = \cos \left (x \right ) \]

3775

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+9 y = 9 \ln \left (x \right ) \]

3776

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+5 y = 8 x \ln \left (x \right )^{2} \]

3777

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x^{4} \sin \left (x \right ) \]

3778

\[ {}x^{2} y^{\prime \prime }+6 x y^{\prime }+6 y = 4 \,{\mathrm e}^{2 x} \]

3779

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = \frac {x^{2}}{\ln \left (x \right )} \]

3780

\[ {}x^{2} y^{\prime \prime }-\left (2 m -1\right ) x y^{\prime }+m^{2} y = x^{m} \ln \left (x \right )^{k} \]

3781

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+5 y = 0 \]

3782

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+25 y = 0 \]

3783

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0 \]

3784

\[ {}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0 \]

3785

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

3786

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

3787

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}+4 x^{2} y = 0 \]

3788

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-1\right ) y = 0 \]

3789

\[ {}y^{\prime \prime }+y = \csc \left (x \right ) \]

3790

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+2 y = 8 x^{2} {\mathrm e}^{2 x} \]

3791

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 8 x^{4} \]

3792

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 15 \,{\mathrm e}^{3 x} \sqrt {x} \]

3793

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 4 \,{\mathrm e}^{2 x} \ln \left (x \right ) \]

3794

\[ {}4 x^{2} y^{\prime \prime }+y = \sqrt {x}\, \ln \left (x \right ) \]

3797

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 4 \,{\mathrm e}^{-3 x} \]

3798

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 4 \,{\mathrm e}^{-2 x} \]

3802

\[ {}y^{\prime \prime }-4 y = 5 \,{\mathrm e}^{x} \]

3803

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 x \,{\mathrm e}^{-x} \]

3804

\[ {}y^{\prime \prime }-y = 4 \,{\mathrm e}^{x} \]

3805

\[ {}y^{\prime \prime }+x y = \sin \left (x \right ) \]

3806

\[ {}y^{\prime \prime }+4 y = \ln \left (x \right ) \]

3807

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 5 \,{\mathrm e}^{x} \]

3808

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

3809

\[ {}y^{\prime \prime }+y = 4 \cos \left (2 x \right )+3 \,{\mathrm e}^{x} \]

3935

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

3936

\[ {}y^{\prime \prime }+4 y = 0 \]

3937

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 4 \]

3938

\[ {}y^{\prime \prime }-y^{\prime }-12 y = 36 \]

3939

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 10 \,{\mathrm e}^{-t} \]

3940

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 4 \,{\mathrm e}^{3 t} \]

3941

\[ {}y^{\prime \prime }-2 y^{\prime } = 30 \,{\mathrm e}^{-3 t} \]